Holden Chester Richardson papers - Richardson, Holden Chester, 1878-
General and family correspondence, speeches, writings, subject file, photographs, and other papers relating primarily to Richardson's activities in aeronautics and naval aviation. Correspondents include James E. Fechet, Ernest Joseph King, Ernest M. Pace, Edward T. Pachasa (later Packard), Carl J. Wenzinger, and Isaac I. Yates.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Aeronautics; Naval aviation; Fechet, James E. -- 1877- -- Correspondence; King, Ernest Joseph, -- 1878-1956 -- Correspondence; Pace, Ernest M. -- Correspondence; Packard, Edward T. -- Correspondence; Wenzinger, Carl J. -- 1903-1988 -- Correspondence; Yates, Isaac I. -- Correspondence; Richardson family -- Correspondence; United States. -- Navy -- Aviation; Naval officers